Formação profissional da pessoa com deficiência : uma experiência da Escola Técnica Federal de Sergipe/Centro Federal de Educação Tecnológica de Sergipe (2001-2007) - Oliveira, José Adelmo Menezes de (2018)
The 20th century was marked by intense struggles and accomplishments in favor of the application of human rights, notably those which aimed at the social groups who were most vulnerable. Dealing with exclusion as well as social inequality also depended upon public policies in education and work. Within this context, the articulation between Special and Professional Education has gained ground during this new millennium as a possible pathway to the Professional training of the disabled person. This articulation has simultaneously raised this group’s literacy levels and widened their possibilities of entering the labor market. From this perspective, this research intends to analyze the process of implementation of the actions for the professional education of the disabled person and its influence upon the school culture of ETFSE/CEFET-SE (or The Federal Technical School of Sergipe, hereinafter referred to as ETFSE/CEFET-SE), between 2001 and 2007. This work, therefore, consists of a qualitative research, namely, a case study that, departing from the theoretical-methodological assumptions of the New Cultural History, employed the concepts of representation and practices in order to better understand the actions undertaken at ETFSE/CEFET-SE for the professional education of the disabled person. For this, we attempted to promote a dialogue among the works by Certeau, Le Goff, Julia, Birklen, Mantoan, Mendes, Glat, Carvalho, Ciavatta, Sacristán, Bardin and Yin. We also analyzed the main pieces of legislation, programs and plans concerned with the education of the disabled person produced both in Brazil and abroad as well as those drafted by the school in question. In a complementary fashion, we carried out semi-structured interviews with managers, members of the Núcleo de Apoio às Pessoas com Necessidades Especiais – Napne (or The Assistance Center for People with Special Needs, hereinafter only Napne), teachers and disabled students who participated in the actions of the Programa de Educação, Tecnologia e Profissionalização para Pessoas com Necessidades Educacionais Especiais - Tec Nep (or The Program of Education, Technology and Training for People with Special Educational Needs, hereinafter Tec Nep), during the period covered by this research. The results provided evidence that the professional education of the disabled person is addressed in an inaccurate, peripheral and diffuse way in the documents of EFTSE/CEFET-SE, which lack a consistent conceptual, methodological, documental and financial basis. It also became evident that the actions for the professional education of the disabled person based themselves less on the notion of inclusion than on the educational segregation paradigm, due to the inadequacy of the main documents and the nearly absolute institutional omission with regard to the actions of the Tec Nep. Therefore, we concluded that, despite the institutional omission, the astute and voluntary practices carried out by the members of Napne, teachers and the disabled students themselves contributed to the incorporation into the school culture at ETFSE/CEFET-SE of elements constitutive of a less excluding educational paradigm.